Penilaian Hasil Pelatihan Mengenal Penyebab Halitosis dan Pencegahannya dengan Pemeliharaan Kesehatan Gigi Mulut pada Warga Apartemen French Walk, Jakarta Utara - Indy Labaron; Dewi L. Margaretha; Yuniar Zen; Rizki; Julia Mustopa; Joanna N. Sumaji (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2022)
Bad breath or halitosis is bad smell that come from mouth, which is a common problem that can cause anxiety and significant psychological distress. Potential causes of halitosis are pseudohalitosis, physiological dan pathological conditions. Usually, people are not familiar about how to differentiate causes, prevention, and treatments oh halitosis. These can affect health issues, discomforts, and distraction for society in doing their daily activities, especially for people in French Walk Apartment RT 11/ RW 19 Kelurahan West Kelapa Gading, North Jakarta. Community health services by Faculty os Dentistry, Trisakti University was done in limitation of Covid-19 Omicron variant outbreak. It’s done on Wednesday, march 2nd, 2022 by Zoom application at 2-3.30pm WIB. There’re 21 participants filled attendance and did 20 pre-post test questions. Participants were given training and simulation on how to brush teeth, dental floss usage, tounge scrapper, and mouth rinsing by committee. The questionnaires provided showed an increase in knowledge and behavior in post test result. By the effective result, hopefully there will be increase in health and quality of life that leads to healhtier Indonesia as well.